Pengaruh Perencanaan SDM yang Efektif terhadap Kepuasan dan Retensi Karyawan - Fadila Ratna Amalia; Yupita Asmul Fauziah; Aisyiah Dwi Puspitasari; Suwandi (CV. ITTC INDONESIA, 2025)
his study aims to examine the effect of effective Human Resource (HR) planning on employee satisfaction and retention. Proper HR planning is expected to enhance job satisfaction and reduce employee turnover within the organization. Data was collected through surveys conducted among employees in several companies, using regression analysis to determine the relationship between HR planning, job satisfaction, and employee retention. The results indicate that effective HR planning has a significant positive effect on employee satisfaction and can improve employee retention within the organization. Therefore, companies need to focus more on appropriate HR planning to create a work environment that supports satisfaction and retains the best employees.